G196 The fear of losing a child!. (25th October 2020) - Skehin, K; Molloy, S; McGrath, A; Thompson, A; Bourke, T; Flannigan, C
Abstract : Background: Paramedics in Northern Ireland are expected to treat unwell children; perform life-saving interventions, in challenging surroundings with limited resources. Surprisingly, Northern Irish paramedic baseline paediatric education is minimal, and reliant on the 'Joint Colleges Ambulance Liaison Committee Clinical Guidelines' and personal experience to provide a solid foundation of knowledge. Furthermore, the Northern Ireland Ambulance Service (NIAS) does not offer subsidised study leave. Approached by a paramedic crew, provoked by a number of tough, emotive paediatric call-outs, we conceived, designed and facilitated a collaborative, bespoke paramedic paediatric study day. Aims: To improve paramedic confidence in the management of unwell children. To provide an insight into hospital–based management of paediatric emergencies aimed to complement paramedic knowledge. To create a multidisciplinary forum for paramedics and paediatricians to network, improve relations and educate via a shared learning environment. Methods: Designed as a regional study day for NIAS members. Recruitment of paediatric intensivists, emergency consultants and senior paediatric trainees to facilitate lectures on emergencies; recognition, interventions and outcomes. Rotating skills stations focused on airway, cardiovascular management and an informative question and answering session. A simulated 'cot death' scenario to amalgamate learning objectives. A paramedic led pre–recorded out of hospital neonatal arrest call, streamed and continued in hospital with the emergency team receiving the patient. An actress played the role of the parent for authenticity. Responses evaluated via feedback forms. Results: This complimentary course was fully subscribed within five hours of advertisement. Fifty-five paramedics attended, 35 provided feedback; 100% felt more comfortable dealing with the unwell child after the course. Greater than 90% rated the skills station and lectures as extremely useful; simulation, validated by the actress was highlighted as 'innovative' and 'enlightening'. Further feedback read 'extremely beneficial day', 'thoroughly enjoyed and learned so much' and 'please, more of these events'. Suggested improvements included a bigger venue and more time. Conclusion: The course will run annually to facilitate regular paramedic training and enhance pre and in-hospital working relationships. The collaborative paramedic paediatric study day is a fabulous opportunity for all to progress in a shared learning environment, mutually respectful of the reality and fear of losing a child!